Forced Migration of Displaced Scholars in the 20th Century and Its Impact in the Circulation of Knowledge and Ideas (Ágora de Heterodoxias, 2022)
This review article is an analysis of forced migration of the displaced scholars and scientists from European universities that arrived in Britain in some periods of the twentieth century, especially during the First and the Second World Wars, and the inter and post-war years; presenting in the final part of this paper, in some detail, how in the contemporary period, the pattern of the academic migration to Britain has changed.
Keywords: Forced migration; Displaced scholars; Britain; Contemporary period; Inter and post-war years